Development of Advanced Artificial Solid Electrolyte Interphases for Lithium Metal Anodes - Krauskopf, Bastian; Justus Liebig University Giessen (My University, 2023)
The electrification of the transport and traffic sector is an important goal for reducing CO2 emissions as part of worldwide efforts to combat global warming. Despite increasing ranges, the limited range and relatively long charging times of electric vehicles (EVs), also known as range anxiety, remain a major reason for their slow adoption. Experts believe that increasing the energy density of batteries to 500 Wh/kg and 1000 Wh/L is crucial to address this issue. However, the current lithium ion battery technology cannot achieve these values due to its physical and chemical limits. Lithium metal batteries offer a promising alternative as they potentially offer higher energy and power densities. Unlike conventional lithium ion batteries with graphite anodes, lithium-metal batteries eliminate carrier materials like graphite in the anode, thereby increasing the specific capacity of the anode material. However, lithium-metal batteries face challenges such as unwanted reactions between the lithium metal anode (LMA) and the electrolyte, which affect both components, as well as uneven lithium growth on the electrode surface, leading to reduced battery life. In this study, various approaches were examined to create a more stable interface between LMA and the liquid electrolyte to prevent degradation reactions and uneven lithium deposition. The first part of the study focused on polymer-based protective layers applied to the anodes using spin-coating. The treated electrodes were investigated in symmetrical transfer cells regarding overvoltage and cycling stability. It was found that adding metal complexes to the polymer significantly reduced overvoltage, and, for example, a hybrid protective layer consisting of polyethylene oxide and the solid electrolyte Li6PS5Cl led to high cycle stability, although the compatibility between the polymer, solid electrolyte, and solvent can be problematic. In the further course of this study, the natural passivation layer of the lithium electrodes was modified via dip coating to obtain an artificial interface with improved homogeneity, conductivity, and stability. The way in which the reagents used for dip-coating reacted with lithium or the passivation layer and how this influenced the performance of the electrodes was examined. In addition to the symmetric cell tests, surface analytical methods such as X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) were applied. It was found that modifications using halogen-containing reagents that react with the electrode surface, for example, to form LiCl or LiBr, resulted in significantly improved lithium dissolution and deposition. Combining a nitrogen and phosphorus-containing compound with a sterically hindered alcohol also resulted in a thin and homogeneous surface layer containing highly ionically conductive Li3N, leading to improved properties in terms of lifespan and capacity loss in both symmetrical cells and lithium-sulfur cells. The results of this study expand knowledge about the possibilities of protective coating and surface modification of LMAs. Important parameters were identified that need to be considered in relation to polymer-based protective layers: the stability of the solid electrolyte towards the solvent, the stability of the solvent towards lithium, and reactions between the polymer and the solid electrolyte. Regarding the dip-coating of the electrodes, it was recognized that desired properties or chemical compositions on the electrode surface can be achieved, for example, by selectively utilizing suitable leaving groups (Cl, Br) and modifying reactivity through the choice of solvent or combination of reagents.
Keywords: Batterie; Lithiummetallanode; Lithium metal anode; Coatings; ddc:540